Becoming Interreligious Towards a Dialogical Theology from a Jewish Vantage Point - Meʾir, Efrayim 1949- (Münster New York Waxmann, 2017)
The present volume contains reflections on the desirability and even the necessity of the interreligious dialogue and of dialogical theology in an increasingly globalized world. A kaleidoscope of various religions, each with its own specificity and cultural singularity, characterizes plural, open societies. In this constellation, encounters with religious others allow us to reimagine and reconfigure our religious singularity. In the process of becoming interreligious, one dynamically and creatively shapes one's particularity in communication with others. The nightmare of a homogeneous society where the other has no place at all receives its alternative in the vision of a growing community in which one's cultural and religious identity is formed, affirmed, and transformed in dialogue with others.
Keywords: Hermeneutics; Hermeneutics; Judentum; Religionswissenschaft; Dialog; Hermeneutik; Schulpädagogik; Interreligiosität; Dialogue; Dialogische Theologie; Dialogical Theology; Interreligiosity; Religion